Deadaption and Readaptation with Lactose, But No Cross-Adaptation to Lactulose: A Case of Occult Colonic Bacterial Adaptation - Andrew Szilagyi; Albert Cohen; Christina Vinokuroff; Darakhshan Ahman; Usha Nathwani; Samara Yesovitch (Canadian Journal of Gastroenterology)
The standard 3 h breath hydrogen (3hBH2) test distinguishes lactose maldigesters from lactose digesters. However, multiple factors impact on BH2 and care is needed to exclude a priori variables. When these factors are controlled, a negative BH2 test implies lactase persistent status or lactase nonpersistent status with colonic adaptation. A case of a Sicilian man who tested negative (lactase persistent status confirmed) on an initial 50 g lactose challenge is described. It was observed that he consumed 28.1 g lactose/day before testing. He subsequently underwent five additional challenge tests in the course of the next 10 months. In four tests the dose intake of lactose was varied upon instruction, and in the fifth test a 30 g lactulose challenge was carried out. It was demonstrated that on radically decreasing lactose intake, a full lactase nonpersistent status was unmasked. Output of 3hBH2 varied inversely with daily lactose intake. Finally, at a time when he was readapted to lactose, there was no discernible adaptation to lactulose challenge. It was concluded that 'occult' colonically adapted subjects may contribute to negative BH2 tests. There is a relationship between variation in lactose intake and the results of BH2 testing. Finally, there was no cross-adaptation to lactulose challenge when lactose was used as the adapting sugar.